2014
DOI: 10.3109/07420528.2014.908898
|View full text |Cite
|
Sign up to set email alerts
|

Daytime restricted feeding modifies the daily variations of liver gluconeogenesis: Adaptations in biochemical and endocrine regulators

Abstract: Daytime restricted feeding (DRF) promotes circadian adaptations in the metabolic processing of nutrients. We explored the hepatic gluconeogenic response in DRF rats by the temporal profiles of the following: (1) the activity of glucose 6-phosphatase (G6Pase) and phosphoenolpyruvate carboxykinase (PEPCK), as well as the periportal and pericentral distribution of PEPCK; (2) conversion of alanine to glucose; (3) glycemia and liver glycogen content; (4) presence of glycogen synthase (GYS) and its phosphorylated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 39 publications
4
42
1
Order By: Relevance
“…Hence, based on reports of physiological consequences of continuous UAG infusion, it is suggested that the high concentration of UAG (which we found to be associated with dRF) could improve glucose metabolism and inhibit lipolysis, thus displaying effects with hypoglycaemic properties (42). Indeed, we have observed a hypoglycaemic state in rats under dRF (43).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Hence, based on reports of physiological consequences of continuous UAG infusion, it is suggested that the high concentration of UAG (which we found to be associated with dRF) could improve glucose metabolism and inhibit lipolysis, thus displaying effects with hypoglycaemic properties (42). Indeed, we have observed a hypoglycaemic state in rats under dRF (43).…”
Section: Discussionsupporting
confidence: 52%
“…The increase of GH seen after feeding (ZT 6 h) in the dRF group is not easy to explain given the proven inhibitory action of insulin on GH secretion . Particularly, the dRF paradigm promotes a large peak of insulin after mealtime at ZT 6 h . A tentative interpretation is that the rheostatic regulation associated with dRF could be altering the signalling by JAK2 and STAT5B, which mediate the inhibitory action of insulin on GH secretion .…”
Section: Discussionmentioning
confidence: 99%
“…DRF promotes a phase shift in BMAL1 and PER1 (2,3) , an oxidised redox state in the mitochondria and cytosol (7) , higher levels of SIRT1 in hepatic cytosol before mealtime, and an elevated presence of cytosolic PGC-1α in the 24-h profile (14) . All these changes are associated with an enhanced 'fasting' response in DRF rats at times before food access (2,3,7,14) . In our results, the nucleus:cytosol ratio of SIRT1 exhibits a peak at the end of the dark phase ( Fig.…”
Section: Circadian Aspectsmentioning
confidence: 99%
“…2(a)) (7) . DRF is characterised by the presence of food anticipatory behaviour (FAB) before mealtime, when the metabolic fasting response is more active in the liver (2,(7)(8)(9)14) . The metabolic products of lipid catabolism, KB (Fig.…”
Section: Circadian Aspectsmentioning
confidence: 99%
“…9 Besides its important biochemical role, GDH has been implicated in pathological conditions such as cancer, hyperinsulinism, and ethanol-induced cell necrosis. [10][11][12] Using a food restriction protocol (2 h of daytime food access for three weeks), we have reported a set of biochemical adaptations in liver mitochondrial activity and metabolic nitrogen-handling responses that could influence GDH functional properties: (1) enhanced mitochondrial synthesis of ATP, 13 (2) reduced mitochondrial lipid peroxidative activity, 14 (3) increased gluconeogenesis and ureagenesis, 15,16 and (4) modified activity and expression of glutamine synthetase and GABA transaminase. 17,18 This protocol has also been used to study an alternative circadian clock, different from the suprachiasmatic nucleus, which is entrained by food access (known as the food entrainable oscillator, FEO).…”
Section: Introductionmentioning
confidence: 99%